Game development with PyGame : write your own games, simulations and demonstrations with Python - Groot, Coen de (Apress, 2019)
"In this video course, you'll learn how to use PyGame, an easy-to-learn Python library, to create interactive experiences such as games, demonstrations, and exercises. You'll start with an overview of PyGame and see how to install it. Next, you'll cover the basics of using programming with PyGame including creating drawing surfaces; the coordinate system and the Rect class to define the location and sizes of images and shapes; the different ways to represent colors; and how to respond to keys and mouse actions. Further, you will see the game loop, another key part of PyGame programming. You then look at examples of PyGame creations, and some of the best places to find images, sounds, and other resources, to help you kick start your own. You will also have access to step-by-step instructions for writing two different simple games. Next, you'll dive into the detail of using PyGame and will cover most of its core functionality. This starts with drawing shapes, such as rectangles, circles, and lines, which can all be surprisingly useful and make a great start for a wide variety of games and other interactive experiences. You will conclude by seeing how to use sound and music in PyGame, from quiet background music to lively explosions. Make a strong start with PyGame by watching the video then access the accompanying example code as a basis for your own games or to confirm your understanding of the different features."--Resource description page